America on the edge : Henry Giroux on politics, culture, and education - Giroux, Henry A. (Palgrave Macmillan, 2006)
For more than 20 years Henry Giroux has challenged readers to address the political exploitation and manipulation of American youth. Now, this compelling new book offers a comprehensive selection of Giroux¿s best works. From his most influential classics to new, never before published essays, America on the Edge offers an overview of Giroux's philosophies throughout his career. From his classic subjects, such as education and democracy and media and youth culture, to revolutionary new views on terrorism, globalization, and morality, this book is essential for all Giroux fans and educators alike. Henry Giroux provides a series of brilliant and provocative essays on the rise of authoritarianism in America, the rise of religious fundamentalism, the crisis of youth, the militarizing of public space, the politics of the Abu Ghraib prison scandal, the rise of the corporate university, the rise of Orwellian newspeak in the media, the emergence of a hard-boiled masculinity in popular culture, and what it means to reclaim hope in dark times. These essays combine important social issues with an accessible and clear language of historical understanding, critique, and possibility. Giroux argues that the United States is in the midst of a political crisis that is slowly undermining the foundation of democratic politics, culture, and education. He also argues that the crisis of politics is matched by a crisis of imagination and that if democracy is going to survive it is imperative to both rethink the nature of democracy while refashioning a new political language and cultural politics capable of both stopping the current turn toward authoritarianism and reclaiming the possibilities of a substantive democracy.